Success of Enterprise Resource Planning Implementation on Sustainable Performance of Logistics Business in Thailand - Kanthana Ditkaew; Laphatrada Pitchayatheeranart; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
This research aims to investigate the influences of the enterprise resource planning implementation on logistics management efficiency and its impact on the sustainable performance of logistics business in Thailand. The data were collected by sampling methodology. There were 520 samples selected from the registered companies conducting business as an entrepreneur of transportation business including both transporting freight and passengers as of the first quarter of 2019. The data were analyzed with the structural equation modeling (SEM).  The findings revealed that the success of enterprise resource planning implementation had direct positive influences on the logistics management efficiency in terms of warehouse management (LME/WH) and transportation management (LME/TM).  The direct positive influences were equivalent to 0.42 and 0.60 respectively which were statistically significant at the 0.01 level. The study of casual relation of logistics management efficiency in four aspects showed that the positive influence on sustainable performance were equivalent to 0.16, 0.03, 0.75 and 0.25 respectively which were statistically significant at the 0.05 level.